The impact of portal pedicle clamping on survival from colorectal liver metastases in the contemporary era of liver resection: a matched cohort study. Issue 9 (September 2015) - Tsang, Melanie E.; Karanicolas, Paul J.; Habashi, Rogeh; Cheng, Eva; Hanna, Sherif S.; Coburn, Natalie G.; Law, Calvin H.L.; Hallet, Julie
Abstract: Introduction: Portal pedicle clamping (PPC) may impact micro‐metastases' growth. This study examined the association between PPC and survival after a hepatectomy for colorectal liver metastases (CRLM). Methods: A matched cohort study was conducted on hepatectomies for CRLM at a single institution (2003–2012). Cohorts were selected based on PPC use, with 1:1 matching for age, time period and the Clinical Risk Score. Outcomes were overall and recurrence‐free survival (OS and RFS). Cox regression was performed to assess the association between PPC and survival. Results: Of 481 hepatectomies, 26.9% used PPC. One hundred and ten pairs of patients were matched in the cohorts. There was no significant difference in OS [hazard ratio (HR) 1.18; 95% confidence interval (CI): 0.76–1.83], with a 5‐year OS of 57.8% (95%CI: 52.4–63.2%) with PPC versus 62.3% (95%CI: 57.1–67.5%) without. Five‐year RFS did not differ (HR 0.98; 95%CI: 0.71–1.35) with 29.7% (95%CI: 24.9–34.5%) with PPC versus 28.0% (95%CI: 23.2–32.8%) without. When adjusting for extent of resection, transfusion, operative time and surgeon, there was no difference in OS (HR 0.91; 95%CI: 0.52–1.60) or RFS (HR: 0.86; 95%CI: 0.57–1.30). Conclusions: PPC was not associated with a significant difference in OS or RFS in a hepatectomy for CRLM. PPC remains a safe technique during hepatectomy.